A structural and functional subdivision in central orbitofrontal cortex - Maya Zhe Wang; Benjamin Y. Hayden; Sarah R. Heilbronner (Nature Communications, 2022)
A portion of the orbitofrontal cortex can be subdivided by its connectivity with the posterior cingulate cortex. This connectivity-based parcellation shows differences in functional connectivity and economic choice signals.